PROPORTION OF RHESUS BLOOD TYPE PHENOTYPES OF ROUTINE BLOOD DONORS AT BLOOD DONOR UNIT INDONESIAN RED CROSS IN BANDUNG CITY - Ivana Dewi; Nadjwa Zamalek Dalimoenthe; Anna Tjandrawati; Nida Suraya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Blood type phenotype incompatibility including Rhesus between donors and patients may result in cross-matching problems, triggering alloimmunization, and causing Hemolytic Transfusion Reaction (HTR). Rhesus blood type incompatibility between mother and fetus may cause Hemolytic Disease of Fetus and Newborn (HDFN). Pretransfusion phenotypic blood groups matching also reduce cost efficiently which means antibody screening is no longer needed. The purpose of the study was to find the proportion of Rhesus blood type phenotypes in routine blood donors at the Blood Donor Unit, Indonesian Red Cross in Bandung city, Indonesia. The study was descriptive and observational with a cross-sectional design. The study was done at the Blood Donor Unit, Indonesian Red Cross in Bandung city from April 2016 to September 2017. The subjects were 142 routine blood donors. Blood sampling was done simultaneously with blood donation. Rhesus antigen examination of ethylenediaminetetraacetic acid (EDTA) blood was done by gel method. Subjects characteristics were males (68%) and females (32%), with the mean age of 39 years. Examination of Rhesus antigen found antigen D(100%), antigen e(98.6%), antigen C(97.9%), antigen c(38.7%) and antigen E(31.7%). Results of Rhesus phenotypes were DCe/DCe(61.3%), DCe/DcE(29.6%), DCe/dce(7%), DcE/DcE(1.4%) and DcE/dce(0.7%). The distribution of Rhesus blood type was affected by factors such as genetics, race, ethnicity, marriage, demography, and migration. Rhesus blood phenotypes proportion in routine blood donors at Blood Donor Unit, Indonesian Red Cross in Bandung city sorted from the most were DCe/DCe, DCe/DcE, DCe/dce, DcE/DcE, and DcE/dce.